HIAPP forms toxic oligomers in plasma. Issue 43 (10th May 2018) - Rodriguez Camargo, Diana C.; Garg, Divita; Buday, Katalin; Franko, Andras; Rodriguez Camargo, Andres; Schmidt, Fabian; Cox, Sarah J.; Suladze, Saba; Haslbeck, Martin; Mideksa, Yonatan G.; Gemmecker, Gerd; Aichler, Michaela; et al.
Abstract : Glucose and lipid containing particles such as LDL interact with hIAPP, resulting in the formation of hIAPP oligomeric structures that yield an intrinsic fluorescence and toxicity in cellular assays. Abstract : In diabetes, hyperamylinemia contributes to cardiac dysfunction. The interplay between hIAPP, blood glucose and other plasma components is, however, not understood. We show that glucose and LDL interact with hIAPP, resulting in β-sheet rich oligomers with increased β-cell toxicity and hemolytic activity, providing mechanistic insights for a direct link between diabetes and cardiovascular diseases.